Teachers' Ability to Apply Higher-Order Thinking Skills in English Lesson Plan - Suardamayasa, Putu (English Education Department STKIP Agama Hindu Singaraja, 2022)
Training students' thinking skills also have an essential role in developing students' abilities in the learning process. To achieve and train students' thinking skills, appropriate planning is needed between teachers and students. This article aimed to find out the profile of the teacher and the obstacles faced by teachers in making lesson plans skills and the process of higher-order thinking skills in the lesson plan class X SMK Negeri 2 Singaraja teacher. This research was designed in a qualitative descriptive research method. The subjects of this study were the English teachers at SMK Negeri 2 Singaraja class X. This research showed that the teacher knows about preparing lesson plans and applying higher-order thinking skills. The teacher can also apply and develop creatively the use of higher thinking skills to the lesson plan to support the learning process.